Incidence of metopic suture in skulls of Northeastern Thai adults - Maneenin, Chanwit; Tungsrithong, Naowarat; Toomsan, Yanyong; Chaiciwamongkol, Kowit; Sripanidkulchai, Kittisak (Biomedical Sciences and Clinical Medicine, 2024)
Objectives To identify the incidence of metopic sutures and their variations in shape, as well as the risk factors in northeastern Thai adults. Methods A cross sectional analytic study was conducted in the Human Anatomy Laboratory at the College of Medicine and Public Health, Ubon Ratchathani University. The skulls of 52 embalmed human cadavers and 27 dry skulls of northeastern Thai adult subjects were examined. Data were collected using a form for record keeping created by an anatomist. The descriptive and inferential statistics were analyzed by SPSS version 16.0 for Windows. Results The skulls studied showed that the occurrence percentage of metopic suture was 20.3%, of which 81.2% were male and only 18.8% female. Metopism was found in 50% of the skulls examined. The frequency found in male skulls (62.5%) was higher than that seen in female ones (37.5%). Incomplete metopic sutures were found in 50% of the skulls, showing morphological variations of a U and V shape, which were seen to be equal in frequency at 25%. Different incidences of metopic sutures were associated with gender and types of subjects. Conclusions This study showed the incidence of metopic sutures in Thai adults, which should be noted for the fields of radiology and forensic medicine.